Temporal variation in demography of the chocoan river turtle, rhinoclemmys nasuta (geoemydidae), on isla palma, malaga bay, pacific coast of valle del cauca (2014)
Few long-term demographic studies have been conducted in freshwater turtles of South America despite the need for this type of inquiry to investigate natural variation and strengthen conservation efforts for these species. In this study, we examined variation in demography of the Chocoan River Turtle (Rhinoclemmys nasuta) based on a population from an island locality in the Colombian Pacific region between 2005 and 2012. At this locality we captured turtles by hand in five streams with a total area of 0.4 ha. We calculated population size with the Jolly-Seber method and compared the population structure of four time periods (2005,2006, 2007, 2011 and 2012). We calculated the probability of survival and capture probability for males, females and juveniles using the Cormack –Jolly-Seber model and we estimated the rate of population growth with the POPAN model. We found increases and decreases in population size, and a significant increase in the percentage of juveniles in 2011 and 2012. In all periods, females dominated the sex structure of the population. Temporal variation in population size may be due to natural changes in habitat or density-dependent effects. However, it may correspond with normal fluctuations in population parameters, therefore continuous monitoring that can be correlated with environmental and physical factors of the habitat could elucidate the causes of the variation.  Variación demográfica temporal de la tortuga de río chocoana, Rhinoclemmys nasuta (Geoemydidae), en Isla Palma, Bahía Málaga, Pacífico del Valle del CaucaPocos estudios demográficos de larga duración han sido realizados en tortugas dulceacuícolas de Suramérica, pese a la necesidad de este tipo de investigación para esclarecer las variaciones naturales y fortalecer procesos de conservación en este grupo particular. En esta investigación se estudió la variación en la demografía de una población de la tortuga de río chocoana (Rhinoclemmys nasuta), a partir de información registrada en una localidad insular del Pacífico colombiano entre 2005 y 2012. En esta localidad se capturaron manualmente tortugas en cinco riachuelos con un área total de 0,4 ha. Se calculó el tamaño poblacional con el método Jolly-Seber en cuatro periodos (2005, 2006, 2007, 2011 y 2012), y se comparó la estructura poblacional. Se estimó la probabilidad de supervivencia y la probabilidad de captura para machos, hembras y juveniles utilizando el modelo Cormack-Jolly-Seber, y la tasa de crecimiento poblacional con el modelo POPAN. Se evidenciaron aumentos y disminuciones en el tamaño de la población. Se evidenció un aumento significativo del porcentaje de juveniles que hacen parte de la población durante el periodo de estudio. En todos los periodos las hembras dominaron la estructura de sexos de la población. Las variaciones temporales en el tamaño poblacional pueden deberse a cambios naturales en el hábitat o a efectos denso-dependientes. Sin embargo, tan solo pueden corresponder a fluctuaciones normales en los parámetros poblacionales, por lo tanto monitoreos continuos donde se puedan correlacionar factores ambientales y físicos del hábitat podrían permitirnos elucidar a que se deben estas variaciones.